PEMANFAATAN MATERI PERJANJIAN KERJA SAMA SEBAGAI MEDIA PEMBELAJARAN PKN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK HOMESCHOOLING - Ahmad Nasir Ari Bowo; Intan Kusumawati (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Stages of Implementation of the Cooperation Agreement Material as a Learning Media for Becoming Three People. The first stage is planning, tutors make plans to implement learning. The second stage is the implementation stage, containing material on international relations through international cooperation agreements, negotiations, the formulation of texts and endorsements so that the contents of the cooperation agreement are agreed. The third stage is evaluation, for learning the results of learning through affective, psychomotor and cognitive. Furthermore, learning outcomes are obtained. Utilization of cooperation agreement material as a learning medium can improve student learning outcomes in PKN learning. The average percentage of student learning outcomes before action is 28%. Furthermore, after the action in the first cycle increased to 34%. Whereas in the second cycle increased to 38%.